EXPRESSION ANALYSIS OF ML237, R2R3 MYB AND OIL_143 GENES THAT AFFECT THE COLD TOLERANCE DURING THE COLD-HARDENING STAGE ON SUCCESSFUL CRYOPRESERVATION OF MENTHA × PIPERITA L. - SELIN GALATALI; TALIP ZENGIN; ERGUN KAYA (Journal of Animal and Plant Sciences, 2024)
Mentha × piperita L., one of the oldest known hybrid species, was formed by the derivation of M. spicata L. and M. aquatica L. Since the plant is a hybrid species, it has sterile seeds and can be propagated vegetatively. The fact that the plant grown in natural and field environments is affected by biotic and/or abiotic environmental conditions keeps the continuity of the species under pressure and this situation requires the germplasm of the plant to be protected as an alternative. The current study aimed to investigate the expressions of ML237, R2R3 MYB and oil_143 genes determined by the bioinformatics blast studies that were effective against the cold tolerance in the M. × piperita at transcriptional level during the cold-hardening which is one of the cryopreservation treatment stages. With this study, it is aimed to obtain basic information that can be useful in cryopreservation studies for these and similar plants to be carried out in the future, and in biotechnological applications to increase viability and regeneration after cryo-storage. According to the T-Test result after the statistical evaluation of the results, a significant increases were observed the ML237, R2R3MYB and oil_143 genes.
Keywords: cold stress; long-term conservation; gene expression; Real-Time PCR